2021
DOI: 10.1109/access.2021.3115554
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of the Covid-19 Vaccine Uptake Determinants From Mining Twitter Data

Abstract: Opinion polls on vaccine uptake clearly show that Covid-19 vaccine hesitancy is increasing worldwide. Thus, reaching herd immunity not only depends on the efficacy of the vaccine itself, but also on overcoming this hesitancy of uptake in the population. In this study, we revealed the determinants regarding vaccination directly from people's opinions on Twitter, based on the framework of the 6As taxonomy. Covid-19 vaccine acceptance depends mostly on the characteristics of new vaccines (i.e. their safety, side … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…113,114 The value of observations gained from these studies further justifies its widespread application in different fields including marketing, politics and, in this case, public opinion and public health. 115,116 Overall, misinformation and the spread of anti-vaccination communities on social media platforms contributes to masking healthy behaviors and promotes practices that contribute to negative health outcomes. While restricting information spread on social media continues to be a complex issue, the findings of this review demonstrate the significant importance of building platforms for disseminating authentic public health messages.…”
Section: Discussionmentioning
confidence: 99%
“…113,114 The value of observations gained from these studies further justifies its widespread application in different fields including marketing, politics and, in this case, public opinion and public health. 115,116 Overall, misinformation and the spread of anti-vaccination communities on social media platforms contributes to masking healthy behaviors and promotes practices that contribute to negative health outcomes. While restricting information spread on social media continues to be a complex issue, the findings of this review demonstrate the significant importance of building platforms for disseminating authentic public health messages.…”
Section: Discussionmentioning
confidence: 99%
“…Fifty-three studies applied social media for topic analysis on COVID-19 vaccination. Topic analysis methods included latent Dirichlet allocation (LDA) topic modeling (n=24) [20,23,25,31,34,35,40,47,50,51,[54][55][56]58,60,61,64,[87][88][89][90][91][92][93], manual coding (n=17) [57,80,[94][95][96][97][98][99][100][101][102][103][104][105][106][107][108], and other algorithms (n=12) [26,43,62,[109][110][111][112][113][114]…”
Section: Topic Analysismentioning
confidence: 99%
“…Liu and Liu [36] showed that the public sentiment on COVID-19 vaccines varied over time and depended on geographic location, and Cotfas et al [13,14] underlined that the general public interest in the vaccination process has presented spikes that can be connected with the major events presented in the media in the selected period. Baj-Rogowska [37] used Twitter data to map the vaccine uptake determinants among Polish users and identified six dimensions with influence on COVID-19 vaccine uptake: access, affordability, awareness, acceptance, activation and assurance.…”
Section: Literature Reviewmentioning
confidence: 99%